Partitioning of dry matter and minerals in Kenyan common guava under salt stress: implications for selection of adapted accessions for saline soils - Chiveu, J.; Ubbenjans, U.; Kehlenbeck, K.; Pawelzik, E.; Naumann, M. (Informa UK Limited, 2020)
Common guava (Psidium guajava L.) is valued for its fruit, which is a source of vitamins, minerals, and natural antioxidants. However, guava production faces salinity challenges globally. Salinity through sodium chloride (NaCl) – 0 mM (control), 10/20 mM (low), 20/40 mM (medium), and 40/80 mM (high) – supplied through a standard Hoagland nutrient solution to 10 genetically diverse guava accessions from Kenya was investigated. Leaf number and dry matter (DM) were significantly reduced at the medium and high salinity levels while root DM remained similar. Root water content increased with rising salinity levels, whereas leaf water content was significantly reduced at the high NaCl level. A decrease in the leaf potassium/sodium (K/Na) and calcium/sodium (Ca/Na) ratios with increasing salinity was observed, possibly due to the high accumulation of Na rather than to the replacement of K and Ca. Leaf phosphorus (P) and sulphur (S) decreased with increasing salinity. Leaf boron (B) and iron (Fe) were significantly reduced only at the high salinity level. Differences among the accessions relative to the accumulation of Na were observed and positively correlated with the DM. Thus, the ability to maintain more DM under salt stress could serve as an indicator for salinity tolerance in Kenyan guava.